2011
DOI: 10.1542/peds.2010-1881
|View full text |Cite
|
Sign up to set email alerts
|

Early Autism Detection: Are We Ready for Routine Screening?

Abstract: BACKGROUND. Autism is a serious neurodevelopmental disorder that has a reportedly rising prevalence rate. The American Academy of Pediatrics recommends that screening for autism be incorporated into routine practice. It is important to consider the pros and cons of conducting autism screening as part of routine practice and its implications on the community. We have explored this question in the context of screening from a scientific point of view. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
75
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 36 publications
1
75
1
1
Order By: Relevance
“…Some scientists and practitioners have questioned whether the evidence relative to general developmental surveillance warrants ASD screening, 7,8 and others have argued that research needs to move beyond risk classification and evaluate longer term outcomes of ASD screening (eg, impact on age of diagnosis, related gains attributable to earlier enrollment in intervention). 9 The uptake of ASD screening into pediatric practice has been modest.…”
mentioning
confidence: 99%
“…Some scientists and practitioners have questioned whether the evidence relative to general developmental surveillance warrants ASD screening, 7,8 and others have argued that research needs to move beyond risk classification and evaluate longer term outcomes of ASD screening (eg, impact on age of diagnosis, related gains attributable to earlier enrollment in intervention). 9 The uptake of ASD screening into pediatric practice has been modest.…”
mentioning
confidence: 99%
“…The American Academy of Pediatrics Council on Children with Disabilities (2006) recommended that pediatricians incorporate autism screening as part of routine practice. However, Al-Qabandi, Gorter, and Rosenbaum (2011) reported that routine screening of all infants may be premature at this time because of a lack of effective screening tools and evidence-based, efficacious practices and because of the need for a cost-benefit analysis of conducting universal early screenings.…”
mentioning
confidence: 99%
“…However reasonable it seems to include standardized instruments for screening for ASD into well child care, the barriers include the accuracy of existing validated instruments (Al-Qabandi et al 2011), the time necessary for screening, the cost of screening, the comfort of the care provider in referrals and management of children with ASD prior to diagnostic referral, and referral resources for diagnosis and treatment in the community (Dosreis et al 2006;Gura et al 2011). Surveillance alone is inaccurate in early identification of autism.…”
Section: Provider Satisfaction With Screening For Autismmentioning
confidence: 99%